2018
DOI: 10.1038/s41467-018-04859-5
|View full text |Cite
|
Sign up to set email alerts
|

Rational Zika vaccine design via the modulation of antigen membrane anchors in chimpanzee adenoviral vectors

Abstract: Zika virus (ZIKV) emerged on a global scale and no licensed vaccine ensures long-lasting anti-ZIKV immunity. Here we report the design and comparative evaluation of four replication-deficient chimpanzee adenoviral (ChAdOx1) ZIKV vaccine candidates comprising the addition or deletion of precursor membrane (prM) and envelope, with or without its transmembrane domain (TM). A single, non-adjuvanted vaccination of ChAdOx1 ZIKV vaccines elicits suitable levels of protective responses in mice challenged with ZIKV. Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 43 publications
1
90
1
Order By: Relevance
“…Here, we developed four MVA-ZIKV vaccines expressing the envelope gene, with or without its transmembrane domain, both in the presence and absence of the prM antigens. In our hands, the use of MVA was not as efficient as the ChAdOx1 counter-parts [17]. MVA-ZIKV vaccine candidates induced modest levels of anti-ZIKV E antibodies after a single vaccination approach and they failed to confer sterile protection.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…Here, we developed four MVA-ZIKV vaccines expressing the envelope gene, with or without its transmembrane domain, both in the presence and absence of the prM antigens. In our hands, the use of MVA was not as efficient as the ChAdOx1 counter-parts [17]. MVA-ZIKV vaccine candidates induced modest levels of anti-ZIKV E antibodies after a single vaccination approach and they failed to confer sterile protection.…”
Section: Discussioncontrasting
confidence: 57%
“…We have previously demonstrated that a non-replicative adenoviral-vectored vaccine expressing ZIKV antigens induces high levels of immunity and protective efficacy in a ZIKV mice challenge model against a ZIKV-BR strain, all upon an adjuvanted, single adenoviral-based vaccine [17]. Here, we explored the suitability of different viral-vectored platforms other than adenoviral-vectored vaccines; the modified vaccinia Ankara (MVA) virus was engineered to express the same antigens that were previously expressed in adenoviral-vectored vaccines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Application of the ChAdOx1 platform to a diverse range of emerging pathogens is supported by multiple studies demonstrating that a single dose of ChAdOx1-vectored vaccine fully protected inbred BALB/c mice, sheep, goats, and cattle from lethal Rift Valley fever, protected 100% of transgenic human dipeptidyl peptidase-4 mice from lethal Middle East respiratory syndrome, and offered inbred BALB/c mice sterilising protection from Zika virus infection [107][108][109][110]. Each of these vaccine candidates has potently induced antigen-specific T-cell responses and high titre neutralising antibodies [107][108][109][110][111].…”
Section: Replication-deficient Chimpanzee Adenovirus Vector Platformmentioning
confidence: 99%